Application of Different Stimulation Targets in the Rehabilitation of Parkinson's Disease Mediated by Transcranial Direct Current Stimulation - ZHU Yulian; XI Chong (康复学报)
Parkinson's disease (PD) is a common clinical neurodegenerative disease with characteristics of numerus motor and non-motor symptoms. Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation method which is considered as a promising treatment method and has shown clinical efficacies in improving bradykinesia, balance function, gait and cognitive function of PD patients. Functional recovery can be promoted by modulating multiple brain regions due to the diversity of PD symptoms and complexity of its pathophysiological mechanisms. Although there are lots of tDCS treatment protocols, a uniform standard is undefined. In this review, we summarized the stimulation targets used by tDCS in PD rehabilitation, which include primary motor cortex (M1), dorsal lateral prefrontal cortex (DLPFC), cerebellum and supplementary motor area (SMA). The M1 region and the left DLPFC region are common targets of anodic excitatory stimulation of tDCS. PD patients could benefit a lot when tDCS treatment was applied at "on" period with a stimulation intensity >1 mA, lasting for 20 min. It can be used alone or in combination with other rehabilitation methods. The research results differed because most studies explored single stimulation effect and there were lack of studies on the effects of repeated stimulation. Moreover, the parameters (targeting area, intensity, duration, frequency, etc.) of tDCS are inconsistent. Future studies on standardized tDCS protocols in treating different symptoms of PD are necessary.